Bringing team improvisation to team adaptation: the combined role of shared temporal cognitions and team learning behaviors fostering team performance - Abrantes, A. C. M.; Passos, A. M.; Cunha, M. P.; Santos, C. M. (Journal of Business Research, 2018)
Change and unpredictability characterize today's business environment. Organizational teams must effectively cope with this reality and ensure that high levels of performance are not compromised. By refining team adaptation with the integration of team improvisation, this study tests a team adaptation temporal framework comprising two processes - team improvised adaptation and team preemptive adaptation. We also investigate the relationships between these constructs and shared temporal cognitions, team learning behaviors, and team performance. We conducted four studies with three different samples, and the results suggest that the two framework constructs are distinct. The results also indicate that team improvised adaptation behaviors mediate the relationship between shared temporal cognitions and team performance, and that team learning behaviors moderate this mediation.